Reduced Frontal Nogo-N2 With Uncompromised Response Inhibition During Transcutaneous Vagus Nerve Stimulation—More Efficient Cognitive Control? - Pihlaja, Mia; Failla, Laura; Peräkylä, Jari; Hartikainen, Kaisa M. (Frontiers in Human Neuroscience, 2020)
We have previously shown invasive vagus nerve stimulation to improve attention and working memory and alter emotion-attention interaction in patients with refractory epilepsy, suggesting that VNS might be useful in the treatment of cognitive impairment. The current research focuses on whether non-invasive, transcutaneous vagus nerve stimulation (tVNS) has similar effects to VNS. Furthermore, we aimed to assess whether tVNS has an impact on cognitive control in general or on underlying brain physiology in a task that mimics everyday life demands where multiple executive functions are engaged while encountering intervening emotional stimuli. Event related potentials (ERP) evoked in such a task, specifically centro-parietal P3 and frontal N2 were used as biomarkers for attention allocation and cognitive control required to carry out the task. A single-blinded, sham-controlled, within-subject study on healthy subjects (n=25) was conducted using Executive Reaction Time Test (RT-test), a Go/NoGo task engaging multiple executive functions along with intervening threat-related distractors while EEG was recorded. tVNS at the left tragus and sham stimulation at the left ear lobe was alternately delivered throughout the task. To assess the impact of tVNS on neural activity underlying attention and cognitive control, centro-parietal P3 and frontal N2 peak amplitudes were measured in Go and NoGo conditions. Task performance was assessed with RTs and different error types reflecting cognitive control in general and distinct executive functions, such as working memory and response inhibition. No significant effects due to tVNS on performance in the Executive RT-test were observed. For N2 there was a main effect of stimulator status and a significant interaction of trial type (Go, NoGo) and stimulator status. Post-hoc analysis revealed that tVNS resulted in a significant reduction of frontal N2 only in NoGo condition. No significant effects were observed for P3 nor were there any effects of emotion. Diminished NoGo-N2 potential along with unaltered task performance during tVNS suggests fewer cognitive control resources were required to successfully withhold a prepotent response. Though caution is warranted, we suggest that tVNS may lead to more efficient neural processing with less resources needed for successful cognitive control, providing promise for its potential use in cognitive enhancement.